THE REPRESENTATION OF PALESTINIANS IN THE SPEECHES OF THREE US REPRESENTATIVES REGARDING THE UN GENERAL ASSEMBLY VOTE ON PALESTINIAN STATEHOOD - Yuliana, Ariska (2013)
Studi ini meneliti representasi Palestina dalam pidato dari tiga perwakilan AS mengenai pemungutan suara tentang elevasi status kenegaraan Palestina di Majelis Umum PBB pada November 2012. Studi ini berfokus pada bagaimana Palestina direpresentasikan serta ideologi yang mendasarinya. Studi ini sebagian besar kualitatif yang didukung oleh beberapa kuantifikasi deskriptif. Data diperoleh dari tiga situs resmi pemerintah AS yang berbeda. Data dianalisis dengan menggunakan pendekatan sociosemantic untuk Analisis Wacana Kritis yang dikemukakan oleh van Leeuwen (2008) yang didukung oleh Transitivity Halliday (2004) sebagai alatnya. Studi ini menemukan bahwa Palestina cenderung direpresentasikan secara negatif oleh para perwakilan AS, mereka juga direpresentasikan secara eksplisit. Hal ini dapat dilihat dari kesenjangan yang sangat lebar antara persentase inklusi (93,46%) dibandingkan dengan persentase ekslusi (6,54%) beserta penggunaan negasi yang ditemukan dalam pidato. Ideologi yang mendasari representasi tersebut diantaranya adalah "kolonialisme" dan keberpihakan. Istilah Kunci: analisis wacana kritis, representasi, transitivity, discourse, text, ideologi Abstract The present study investigates the representation of Palestinians in the speeches of three US representatives during the UN General Assembly vote on Palestinian statehood on November 2012. It focuses on the ways the Palestinians are represented in the speeches and the ideologies underlying the representation. This study is largely qualitative supported by some descriptive quantification. Data were obtained from three different official sites of the US government. Data were analyzed by utilizing sociosemantic approach to Critical Discourse Analysis proposed by van Leeuwen (2008) supported by Halliday's (2004) Transitivity as the tool. The study finds that Palestinians tend to be represented negatively by the US representatives; they are also represented explicitly. It can be seen from the extremely wide gap between the percentage of inclusion (93,46%) compared to the percentage of exclusion (6,54%) along with the use of negation evidenced in the speeches. The ideologies underlying the representation involve "colonialism" and partiality. Key terms: critical discourse analysis, representation, transitivity, discourse, text, ideology